Analisis Mobilitas Permanen Tenaga Kerja PT. Pertamina (Persero) di Kelurahan Komperta Kecamatan Plaju Kota Palembang Sumatera Selatan Tahun 2015 - Kurniawati, Indah, Drs. Priyono, M.Si, Dra. Umrotun, M.Si (2016)
The development of industrial sector in an area will bring the influence toward area's development and will bring out people movement. The permanent mobility process in komperta district not only caused by economy factor but also from the narrow working opportunity factor. mobility which happened in Komperta district not only influenced by economy factor. The aim of the study are (1) analyzing the characteristic of offender mobility in komperta district; (2) analyzing the influenced factors of PT. Pertamina (Persero) 's employee whom did mobile in Komperta district. Exploring the pull factor and push factor of mobility. The methods of the study used survey method by individual permanent mobility unit analysis. The respondent of this study is the individual of offender mobility in Komperta district with quota sampling. Descriptive analyzing technique is used in this study by collecting the reliable source of the primary data . The result of the study showed that the existence of PT. Pertamina (Persero) in Komperta district gives a new influenced in the employee's mobility of Plaju region in Komperta district. The employee from outside region (Plaju region) decided to do permanent mobility as (38 respondent or 82.22%) with caption move. While the offender mobility with no caption move as ( 7 respondents or 17.77%). The main push factor of this permanent mobility is caused by the narrow opportunity outside agriculture sector (19 of 45 respondents or 42.22%). While the main pull factor of this study is the economy with high incomes as ( 20 of 45 respondents or 44.44%). Komperta district has a big role in absorption capacity of employee that is caused by the industrial existence in this area, so it improves the standard of living of the people and it also improve the economy of the offender mobility.